Climate change effect on sour cherry production in Central Hungary - Mézes, Z. (International Journal of Horticultural Science, 2016)
Consideration of the soil and climatic conditions and their expected changes is very important in planning of new orchards. This research focuses on the expected climatic conditions and opportunities of sour cherry production in Central Hungary in the periods of 2021–2050 and 2071–2100, compared to the base period of 1961–1990. Results show that in the near future the expected changes are mostly favourable for sour cherry production, the utility values are increasing in most of the subregions. By the end of the century the utility values show further increase in the formerly colder subregions. However, in some subregions the utility values slightly decrease because of the appearance of the extreme dry and warm year types, though their values remain at the level of the base period or even higher.